Dr. Jonas Basanavičius (1851–1927) and his nervous disease - A. Ulytė; E. Sakalauskaitė-Juodeikienė (Neurologijos seminarai)
Doctor Jonas Basanavičius (1851–1927) was the patriarch of the Lithuanian nation, activist in the Lithuanian national revival, a physician, politician, scholar, and editor of the first Lithuanian-language newspaper Auszra. In his autobiography “The Chronicle of My Life and the History of a Nervous Disease” (1851–1922), Basanavičius not only presented the realities of social, political, cultural and academic life of the second half of the XIXth and the beginning of the XXth centuries in Lithuania and Europe but also depicted and analyzed symptoms of his nervous system disease. J. Basanavičius suffered from various episodic ailments – headache, insomnia, deafness, olfactory and gustatory impairments, cardiac arrhythmias, leg pain, paraesthesias, and urinary disorders which he attributed to neurasthenia. In this article we present Basanavičius’s complaints, symptoms, and diseases in chronological order. Medical terms, diagnoses and treatment methods are analyzed in the context of the described historical period and compared to how the terms are used today.